HUBUNGAN PENGETAHUAN, SIKAP DAN PERILAKU HIGIENE SANITASI MAKANAN DENGAN KEJADIAN KESAKITAN PADA SANTRIWATI DAN PENJAMAH MAKANAN DI PONDOK PESANTREN DINIYYAH PUTRI LAMPUNG TAHUN 2024 - Salwa Dara B; Ajib Jayadi; Adhi Nurhartanto (JURNAL ILMIAH NUSANTARA, 2024)
Food-borne illness, also known as foodborne disease, is a health problem or illness caused by consuming food that has been contaminated with physical, chemical, microbiological or allergen contamination. This disease can be caused by various factors, such as food that is not cooked properly, food that is contaminated with bacteria or viruses, or food that contains dangerous chemicals. It is important to practice proper food handling and hygiene techniques to prevent the spread of foodborne illnesses and ensure everyone's health safety. Method : This type of research is quantitative research using a cross sectional design. In this research, the technique used is proportioned random sampling technique. The sample was 112 samples at the Diniyyah Putri Lampung Islamic Boarding School. The instrument of this research is a questionnaire sheet. The test carried out was the chi square test. Results and suggestion : There is no relationship between knowledge and the incidence of illness with value p-value 199, there is a relationship between attitudes and the incidence of illness with values p-value 0,038, there is a relationship between food sanitation hygiene behavior and the incidence of illness with values p-value 0,000. Suggestions require standardization of knowledge, attitudes and behavior regarding food hygiene and sanitation as well as clean and halal certification in Islamic boarding schools.